Cigarette smoke induces endoplasmic reticulum stress-associated mucus hypersecretion via orosomucoid 1-like protein 3 in airway epithelia - Chen, Rui; Cui, Yuting; Ip, Mary Sau-Man; Mak, Judith Choi-Wo (Free radical research, 2025)
Apart from a strong association with childhood-onset asthma, orosomucoid 1-like protein 3 (ORMDL3), an endoplasmic reticulum (ER)-localized transmembrane protein, is also linked with chronic obstructive pulmonary disease (COPD), in which cigarette smoke (CS) is the crucial risk factor. Compared to healthy subjects, COPD patients had elevated ORMDL3 mRNA in well-differentiated primary human bronchial epithelial cells (HBECs). However, its role in COPD remains understudied. We, therefore, hypothesize that ORMDL3 may play an essential role in CS-induced chronic mucus hypersecretion and inflammation activation of specific unfolded protein response (UPR) pathways under ER stress in primary HBECs. Gene silencing using siRNA for ORMDL3 was performed in submerged culture of primary HBECs before 24-h cigarette smoke medium (CSM) exposure. The mucin, inflammatory and mitochondrial markers, and the activation of the UPR pathways were evaluated. CSM triggered significant induction of ORMDL3 expression at both mRNA and protein level, which was significantly inhibited by silencing ORMDL3. In addition, ORMDL3 knockdown inhibited CSM-induced mucin MUC5AC mRNA and release of inflammatory marker interleukin (IL)-8. Silencing ORMDL3 reduced CSM-induced ER stress inhibiting the activating transcription factor (ATF)6 and the inositol-requiring enzyme (IRE)1 of the UPR pathways. The involvement of ORMDL3 was demonstrated in mitochondrial dynamics fusion protein Mfn2 and mitochondrial respiration after CSM stimulation. In conclusion, ORMDL3 is an inducible gene in mediating CS-induced activation of specific ATF6 and IRE1 pathways to regulate mucus hypersecretion and inflammation. Therefore, ORMDL3 may be a promising therapeutic target to treat smoking-associated mucus hypersecretion and inflammation in COPD.